Efficient Investigation of Rock Crack Propagation and Fracture Behaviors during Impact Fragmentation in Rockfalls Using Parallel DDA - Lu Zheng; Yihan Wu; Wei Wu; Hong Zhang; Xinyan Peng; Xuelue Zhang; Xuezhen Wu (Advances in Civil Engineering)
The study of the rock crack propagation and fracture behaviors during impact fragmentation is important and necessary for disaster evaluation of rockfalls. Discontinuous Deformation Analysis (DDA) incorporating virtual joints can offer a powerful tool to solve such a problem. In the analysis process, the computational efficiency is critical because the mesh must be very dense to make crack propagation more realistic. Thus, parallel DDA using OpenMP is applied. The flattened and precrack Brazilian disc tests are first reproduced, respectively, to verify the accuracy and efficiency of the parallel DDA with virtual joints. Then, the impact fragmentation process is simulated and validated with corresponding laboratory experiments in terms of crack propagation results. Furthermore, the effects of joint-slope angle, joint connectivity rate, and impact velocity on rock fracture behaviors are investigated. It is concluded that the peak number of cracks occurs when the joint-slope angle ranges between 30° and 45°; the higher impact velocity and joint connectivity rate tend to cause more cracks and larger damages to the specimen.